An error elimination method for high-temperature digital image correlation using color speckle and camera. (May 2019) - Bao, Siyuan; Wang, Yonghong; Liu, Lu; Lu, Yu; Yan, Peizheng
Highlights: We propose an error elimination method for thermal disturbance in high-temperature environment using color speckle and camera instead of traditional industrial camera. This measurement method is simpler and easier, and the accuracy and practicability of the measurement are higher than the existing methods. All the advantages of digital image correlation method, including simple structure, non-contact and full field measurement. No stringent synchronization is required because what we process is the grayscale information of different channels of each picture. Suitable for any complex high temperature environment. Abstract: Digital image correlation method is a kind of displacement and strain measurement technique based on visible light illumination. It can realize non-contact and full-field measurement with lower requirements on the measurement environment, thus it's widely used in testing and research for mechanical properties of materials at high temperature. But there are many factors affecting the measurement accuracy due to the complexity of the high temperature environment, of which the influence of the thermal disturbance on digital image correlation method is the most obvious. In order to reduce the influence of it and improve the measurement accuracy, this paper proposes a measurement method for eliminating thermal disturbance error in high temperature deformation measurement based on color speckle and camera. Two kinds of grayscale field information of different colors were endued to the surface of specimen, and we collected images by color camera with channel separation for each frame of them. Then we processed the grayscale field of two channels separately combined with the digital image correlation method, analyzed the information carried by two different grayscale fields, and a simple mathematical model was performed to separate the thermal disturbance error from the measurement results. Finally, we set up the experimental system, built the mathematical model between the two channels through static measurement experiment, which was used to extract and correct the thermal disturbance error of measurement results of the rigid body motion experiment. The high consistency between corrected result and true displacement value proved the feasibility and accuracy of the proposed method.